A comparison of enriched culture and Xpert polymerase chain reaction assay of Group B streptococcus carrier status at 35–37-week gestation to labor onset: a prospective controlled study. (18th August 2018) - Perlitz, Yuri; Ben-Ami, Moshe; Megory, Emanuel C.; Nitzan, Orna; Bouganim, Tal; Younis, Johnny S.; Shapso, Nora; Peretz, Avi
Abstract: Objectives: (1) To compare the accuracy of vagino-rectal enriched culture (EC) and a rapid polymerase chain reaction (PCR) test for the detection of Group B streptococcus (GBS) carrier status at 35–37-week gestation and at onset of labor. (2) To assess the conversion rate of GBS carrier status between 35–37 weeks to the onset of labor according to the EC/PCR tests. A prospective study was performed at a women's health clinic, referred to give birth at one medical center. Study population: Low risk pregnant women at 35–37-week gestation who did not know their GBS carrier status. Methods: Participants were evaluated for GBS status both at 35–37 weeks and at labor onset. Correlation between tests was calculated by Spearman correlation. Results: One hundred and ten specimens were analyzed. Correlations: EC-PCR: 35–37 weeks – very high ( r = 0.8), at labor – high ( r = 0.5). EC-EC: 35–37 weeks and at labor – high ( r = 0.39); PCR-PCR: 35–37 weeks and at labor- high ( r = 0.7). Conclusions: Both the EC and Xpert PCR tests are accurate for detecting GBS carrier, both at 35–37 weeks and at labor onset. We did not detect a significant conversion of the GBS status from negative at 35–37 weeks to positive at onset of labor.